Physico-chemical, photo-catalytic and O-2-adsorption properties of TiO2 nanotubes coated with gold nanoparticles - Malwadkar, Sachin S.; Gholap, Ramkrishna S.; Awate, Shobhana V.; Korake, Prakash V.; Chaskar, Manohar G.; Gupta, Narendra M. (Journal of Photochemistry and Photobiology A-Chemistry, 2009)
Gold-containing titania nanotubes (Au/NT) were found to display higher activity for photooxidation of acetaldehyde, as compared to corresponding gold-free nanotubes and also a Degussa P-25 catalyst. Besides CO2 as a major reaction product, small amounts of H-2, CH4, CO, H2O and CH3COOH were also formed, irrespective of the catalyst employed. High-resolution TEM examination showed that most of the gold particles in Au/NT were of 1.5-5 nm size, distributed both within and at outside surface of the nanotubes. Some larger size (10-70 run) clusters were also seen at the external surfaces, particularly in the samples calcined at an elevated temperature. The temperature-programmed desorption measurements revealed that, compared to P-25 TiO2, a significant entrapment of O-2 occurred at two distinct tubular sites of NT samples, corresponding activation energy of desorption (E,) being around 36 and 41 kcal mol(-1). On the other hand, gold nanoparticles in Au/NT served as independent low-energy (E-a = 26 kcal mol(-1)) sites for adsorption/activation of O-2. These adsorptive properties of TiO2 and Au were lost completely on calcination, thus revealing a crucial role played by the particle size. In situ IR spectroscopy results showed that room-temperature exposure to acetaldehyde + air gave rise to a molecularly bound state, i.e. CH3CHOad, over both NT and Au/NTsamples, which in turn transformed quickly to yield certain acetate (CH3COOad-) and formate (HCOOad-) type transient species with the involvement of the surface OH groups. The decomposition and oxidation of these surface species with the help of O-2(-), O-ad and hydroxyl ion radicals (OH-) formed at photo-excited Au/NT interfaces led to the reaction products mentioned above. We conclude that, besides electron-hole charge separation, the adsorptive properties of host matrix and nanosize gold may together play a significant role in deciding the photo-catalytic properties of Au/TiO2. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Acetaldehyde oxidation; Gold co-catalyst; O-2-adsorption; Photo-catalytic activity; TiO2 nanotubes

Photodegradation of methanol under UV-visible irradiation by titania dispersed on polyester cloth - Bhattacharyya, Kaustava; Tripathi, Arvind K.; Gupta, Narendra M.; Tyagi, Avesh K. (Photochemistry and Photobiology, 2010)
Titania supported on polyester fabric (TiO(2)-PY) with varying titania loadings (2-7 wt%) were prepared via the dip-coating method at room temperature using an aqueous slurry of anatase titania. Structural and morphological characterizations by X-ray diffraction and scanning electron microscopy revealed that the titanium dioxide crystallites deposited on the surface of the polyester fabric were in the micrometer range while their phase remained to be anatase. Photocatalytic activity of TiO(2)-PY fabric catalysts was evaluated for vapor-phase oxidation of methanol in air as a test reaction in the presence of UV as well as solar radiation under ambient conditions. These catalysts were found to be quite active in both UV and solar irradiation with activity being higher in the former case. CO(2) yield from photo-oxidation of methanol depended on titania content and also on its dispersion over polyester fabric support.

Preparation-method-dependent morphological, band structural, microstructural, and photocatalytic properties of noble metal-GaNbO4 nanocomposites - Devi, Suman; Kelkar, Sarika A.; Kashid, Vikas; Salunke, Hemant G.; Gupta, Narendra M. (RSC Advances, 2013)
We report the distinct physicochemical and photophysical properties of gallium niobate photocatalysts (bandgap: similar to 3.1 eV), prepared by a solid-state (SS) reaction and sol-gel (SG) method and dispersed with a noble metal (similar to 0.5% of Pt, Au, or RuOx) cocatalyst. SG-GaNbO4 comprised smaller size particles (similar to 20-50 nm) and a larger surface area (similar to 160 m(2) g(-1)) compared to SS-GaNbO4 (particle size similar to 30-150 nm, surface area similar to 27 m(2) g(-1)). XRD patterns revealed a preparation-dependent variation in the relative intensity of prominent reflections. In TEM examination, SG samples exhibited small-range grain boundaries and heterogeneous metal/substrate interfacial contacts, while SS-GaNbO4 had long-range ordering. Laser-Raman and thermoluminescence investigations revealed that lattice distortion, defect-induced inter-bandgap charge trapping states, and the local environment around the metal/semiconductor interfaces may also depend on the preparation method. Metal-GaNbO4 nanocomposites showed no activity for the dissociation of pure water under UV (>250 nm) irradiation, despite the favourable conduction and valence band potentials. This was attributed to the sharp Ga and Nb d-levels in the narrow conduction band of GaNbO4, as confirmed by ab initio electronic structure calculation. These photocatalysts, however, showed good activity for semiconductor-mediated photo-dissociation of aqueous methanol to produce H-2; a cocatalyst-dependent activity trend, Pt > RuOx > Au, was observed. Doping of S at similar to 5% of the oxygen sites led to decreased photoactivity, ascribed to the presence of localized S 3p states just above the O 2p valence level. In conclusion, besides band characteristics, certain morphological and microstructural properties play a crucial role in the photoactivity of the metal/oxide nanocomposites.

Photophysical, bandstructural, and textural properties of o-FeNbO4 in relation to its cocatalyst-assisted photoactivity for water oxidation - Babu, Robin; Kelkar, Sarika A.; Kashid, Vikas; Achary, Srungarpu N.; Salunke, Hemant G.; Gupta, Narendra M. (RSC Advances, 2014)
In this study, a relationship between physicochemical, photophysical and photocatalytic properties of hydrothermally synthesized orthorhombic iron niobate (FeNbO4) is investigated. o-FeNbO4 displayed a multi-regime optical absorbance, which was ascribed to at least two distinct phenomena: (i) bandgap (similar to 3.4 eV) excitation giving rise to UV absorbance and (ii) energy transitions involving disorder-induced sub-bandgap donor or acceptor states leading to visible light absorbance. The preparation-dependent distortion in the crystal lattice and the existence of closely spaced inter-bandgap energy states were corroborated by powder X-ray diffraction, photoluminescence, thermoluminescence, and Raman spectroscopy studies. The first principles electronic structure elucidation and photoelectrochemical measurements supported a wide bandgap for FeNbO4, in contrast to the narrow bandgap reported previously. Correspondingly, a small photocurrent density was observed for FeNbO4 (similar to 2 to 3 mu A cm(-2)) under 1 sun illumination, suggesting the availability of a smaller cross section of photogenerated charge pairs. Following these band characteristics, while no H-2 evolution was observed, FeNbO4 gave rise to particle size-dependent O-2 evolution during visible light irradiation of water in the presence of electron scavengers, the samples loaded with NiO as cocatalyst showing better activity. Further, the transmission electron microscopy examination revealed the dominant exposure of (011) facets of FeNbO4, besides a significant heterogeneity of inter-domain boundaries. Overall, our results confirm that the photoactivity of metal/oxide nanocomposites is governed by a combination of factors, such as: grain morphology, microstructure, surface adsorption states, and the localized inter-bandgap energy states. Our study also reveals that, in contrast to prevalent assumptions, the wavelength at the absorption edge may not represent the true band-to-band energy gap of metal oxide semiconductors, which is relevant to their photocatalytic activity.